2018
DOI: 10.1017/jog.2018.75
|View full text |Cite
|
Sign up to set email alerts
|

Glacier branch lines and glacier ice thickness estimation for debris-covered glaciers in the Central Tien Shan

Abstract: Information about the ice volume stored in glaciers is of high importance for sustainable water management in many arid regions of Central Asia. Several methods to estimate the ice volume exist. However, none of them take the specific characteristics of flat terminus debris-covered glaciers into account. We present a method for deriving spatially-distributed ice thickness for debris-covered dendritic glaciers, which are common not only in Central Tien Shan but also in several other mountain ranges in High Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Future lake developments were estimated using GlabTop (Linsbauer and others, 2016). The bed overdeepenings at slow flowing termini could be slightly overestimated by GlabTop as the flow of glaciers is not considered in this model (Pieczonka and others, 2018). Uncertainties in the overdeepenings can result from the resolution and offset between SRTM DTM and the glacier outlines.…”
Section: Discussionmentioning
confidence: 99%
“…Future lake developments were estimated using GlabTop (Linsbauer and others, 2016). The bed overdeepenings at slow flowing termini could be slightly overestimated by GlabTop as the flow of glaciers is not considered in this model (Pieczonka and others, 2018). Uncertainties in the overdeepenings can result from the resolution and offset between SRTM DTM and the glacier outlines.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the basal shear stress along the central flowlines is set equal to an average yield stress ( τ y ) which is calibrated with the measured ice thicknesses based on the following relations:with α the local surface slope and ρ the average ice density (900 kg m −3 ). Following Li and others (2012) and Pieczonka and others (2018), a shape factor ( f ) is introduced to account for the drag by the valley walls. For simplicity, we assume a constant of 0.8, similar to the value used for the consensus estimate (Farinotti and others, 2019) and in the parametrization scheme of Haeberli and Hoelzle (1995).…”
Section: Ice Thickness Modelling In Unmeasured Areasmentioning
confidence: 99%
“…Previous studies showed that Eqn (5) tends to overestimate the ice thickness in very flat regions (small slope). Therefore, we implemented a minimum slope of 5% (Farinotti and others, 2009, 2017; Carrivick and others, 2016; Pieczonka and others, 2018). However, we do not observe slopes smaller than 5% at the reconstruction points.…”
Section: Ice Thickness Modelling In Unmeasured Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…a −1 during 1999−1 during -2007−1 during (Shangguan et al, 2015, with surface-flow velocities in its upper part being faster than those on its lower part (Nobakht et al, 2014;Shangguan et al, 2015). The estimated maximum thickness is 380 m, and the mean thickness of its debris-covered part is 136 m (Pieczonka et al, 2018). Many supraglacial lakes have developed on its debris-covered area with an annual seasonal drainage cycle (Narama et al, 2017).…”
Section: Study Areamentioning
confidence: 99%